2014
DOI: 10.1155/2014/195053
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Relief Demands in an Emergency Supply Chain System under Large-Scale Disasters Based on a Queuing Network

Abstract: This paper presents a multiple-rescue model for an emergency supply chain system under uncertainties in large-scale affected area of disasters. The proposed methodology takes into consideration that the rescue demands caused by a large-scale disaster are scattered in several locations; the servers are arranged in multiple echelons (resource depots, distribution centers, and rescue center sites) located in different places but are coordinated within one emergency supply chain system; depending on the types of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…Additionally, Kwon & Kim (2018) in south Korea have interpreted that any investing on preparedness stages is much more effective than costing for utilizing relief actions [ 42 ]. In a study conducted in China, it is demonstrated that an emergency supply chain needs to determine supply points, emergency logistic centers and demand points in order to respond quickly [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kwon & Kim (2018) in south Korea have interpreted that any investing on preparedness stages is much more effective than costing for utilizing relief actions [ 42 ]. In a study conducted in China, it is demonstrated that an emergency supply chain needs to determine supply points, emergency logistic centers and demand points in order to respond quickly [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous research studies, the studies about rescue in emergency mainly include rescue methodology [16], rescue architecture [17,18], accessibility of emergency service [19], emergency resource allocation [20][21][22][23][24][25][26][27][28], the determination of the medical rescue demand [29], the prediction of the emergency material demand [9][10][11][12][13][14][15], fre rescue prediction [30], emergency rescue location model [31], emergency rescue service model [32], and rescue performance [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…He and Hu (2014) propose a model for decision-making in disaster prevention systems for the Shanghai area, while Beard and Chamberlain (2013) employ the principles proposed in Pourbabai. et al (1996) for the analysis of the flow of information in computer network systems.…”
Section: Introductionmentioning
confidence: 99%